Exhausting, but necessary: the lived experience of participants in an intensive inpatient trauma treatment program - Vaage-Kowalzik, Veronica; Engeset, Jeanette; Jakobsen, Marianne; Andreassen, Wenche; Evensen, Julie Horgen (Frontiers in Psychology, 2024)
Background Intensive inpatient treatment programs have shown robust results in the treatment of post-traumatic stress disorder (PTSD). How patients experience this treatment program and what changes they experience as a result of the treatment have, however, only scarcely been explored through qualitative studies. Objective This study aimed to explore the lived experience of participants in an intensive inpatient trauma treatment program. Our research questions were as follows: how do patients experience intensive trauma-focused treatment? How do they experience possible changes related to participating in the treatment program? Methods Six patients diagnosed with PTSD with significant comorbidities, who recently participated in an intensive 2-week (4 + 4 days) inpatient trauma treatment program with prolonged exposure (PE), eye movement desensitization and reprocessing (EMDR), and therapist rotation (TR), were interviewed with a semi-structured qualitative interview. Transcripts were analyzed using a thematic analysis approach. Results Our analysis resulted in five main themes: (1) the need to feel safe; (2) the benefits of many and different therapeutic encounters; (3) variable experience with elements of treatment; (4) intensity; and (5) experienced change. Our results suggest that feeling safe within the framework of the treatment program facilitated the treatment process. Many and different therapeutic encounters, both through TR and with ward staff, contributed to experienced change. All participants described the intensity as facilitative to trauma processing. However, most participants also describe often feeling too overwhelmed to benefit from all elements of the treatment program. Conclusions Our findings suggest that participants experience the overall treatment program as beneficial and contributing to experienced change. Participants described the intensity of the program as exhausting, but necessary. Most did, however, report at times of being too overwhelmed to benefit from elements of the program. Consequently, our results prompt us to question the optimal level of intensity. Trial registration ClinicalTrials.gov identifier: NCT05342480. Date of registration: 2022-04-22.